DETERMINAN KINERJA KEUANGAN DAERAH PADA PEMERINTAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Rahmadani, Nurul Annisa; Sarikadarwati; Berlianti, Maulidia (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to determine the elements that influence the financial performance of district/city governments in South Sumatra Province with the independent variables of Balancing Funds, Capital Expenditures, and Wealth Level. The data for this study were obtained from the regional government financial reports (LKPD) in the form of the 2019-2023 Budget Realization Report, which was accessed online through the official website https://e-ppid.bpk.go.id/. Hypothesis testing was conducted using the SPSS version 26 program, which uses multiple linear regression analysis techniques and a value-for-money-based performance measurement approach, which includes elements of economics, efficiency, and effectiveness of public budget use. The research findings show that Balancing Funds do not affect the economic ratio, but have a significant negative effect on efficiency and a significant positive effect on the effectiveness ratio. On the other hand, the Capital Expenditures variable does not show any effect on the economic and effectiveness ratios, but has a significant positive effect on efficiency. Wealth Level does not affect the three indicators. Overall, the three variables only have a significant effect on the efficiency ratio, while there is no apparent effect on the economic and effectiveness ratios. Keywords: : Balanced Fund, Capital Expenditure, Wealth Level, Regional Financial Performance, Value For Money.